2015
DOI: 10.1136/jech-2015-205627
|View full text |Cite
|
Sign up to set email alerts
|

Is young fatherhood causally related to midlife mortality? A sibling fixed-effect study in Finland

Abstract: The findings suggest a causal effect of young fatherhood on mortality and highlight the need to support young fathers in their family life to improve health behaviours and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Previous studies which have analysed samples of men or women have shown that younger parents have worse health in terms of mortality,1 2 6 27 heart disease2 28–30 and cancer,2 and our study extends this work to objectively measured cardiovascular risk factors. Unlike our study, few of the previous studies have accounted for mediation through socioeconomic position, health behaviours and other adult factors, such as work and partnership status, instead often including either health behaviours or socioeconomic position.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies which have analysed samples of men or women have shown that younger parents have worse health in terms of mortality,1 2 6 27 heart disease2 28–30 and cancer,2 and our study extends this work to objectively measured cardiovascular risk factors. Unlike our study, few of the previous studies have accounted for mediation through socioeconomic position, health behaviours and other adult factors, such as work and partnership status, instead often including either health behaviours or socioeconomic position.…”
Section: Discussionsupporting
confidence: 56%
“…Most previous research has focused on the health of women; however, more recently, work on age at first birth and later health has been extended to look at the long-term health of young fathers. A recent study showed that young fatherhood was associated with higher mortality in Finland largely due to cardiovascular disease and higher allostatic load in England 6 7. Research comparing men and women is useful for unpicking biological versus other explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Non-normative, i.e. too early, timing of entering parenthood is suggested to cause stress particularly among women due to conflicting time demands (Bacon, 1974), but normatively too early parenthood may cause stress also for men (Einiö, Nisén, & Martikainen, 2015;Sigle-Rushton, 2005). Delay of parenthood may reduce this stress, and leave more time to complete other transitions to adulthood, including attainment of education.…”
Section: Delay Of Parenthood and Educational Outcomesmentioning
confidence: 99%
“…Two recent studies using SFE with Finnish and Swedish register data extend this result to mortality, although both are based on sibling rather than twin data (Barclay et al 2016;Einio, Nisen & Martikainen 2015). Einio, Nisen and Martikainen (2015) address the relationship between AFB and Finnish fathers' mortality risk, and find that older AFB is negatively related to mortality, with little difference between ordinary survival models and the SFE variant.…”
Section: Empirical Literature Reviewmentioning
confidence: 96%
“…Einio, Nisen and Martikainen (2015) address the relationship between AFB and Finnish fathers' mortality risk, and find that older AFB is negatively related to mortality, with little difference between ordinary survival models and the SFE variant. Barclay et al (2016) similarly find that early first birth timing contributes to higher mortality risk, for Swedish men and women, and for all-cause mortality as well as mortality caused by neoplasms, diseases of the circulatory system, external causes, and other causes.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%